How Organizational Justice Drives Innovative Behavior: Insights from Public Sector Organizations - Theresia Martina Oktadiana; Syamsul Hadi; Didik Subiyanto; Saizal Bin Pinjaman (Researchgate, 2025)
This study was conducted to determine the role of organizational justice on innovative behavior at the Investment and One-Stop Integrated Service Office of Sleman Regency and Bantul Regency. This study is quantitative. The population in this study consisted of government employees of the Investment and One-Stop Integrated Service Office of Sleman Regency and Bantul Regency. The sample used in this study was 67 respondents. The sampling technique in this study was nonprobability sampling using a census. Data collection was carried out by distributing questionnaires. At the same time, the analysis tool used was SPSS Version 25, and data testing with SmartPLS 4.1.0 software. The results of this study indicate that organizational justice has a significant positive effect on innovative behavior. If organizational justice is implemented effectively, it will impact increasing innovative behavior. This study provides new insights into the relationship between organizational justice and innovative behavior, as research discussing these variables is still limited. The application of organizational justice can increase innovative behavior. Organizations that implement justice for their employees will increase innovative behavior.